2006
DOI: 10.1089/apc.2006.20.97
|View full text |Cite
|
Sign up to set email alerts
|

Religious Beliefs, Practices and Treatment Adherence Among Individuals with HIV in the Southern United States

Abstract: Nonadherence with medical treatment is a critical threat to the health of those living with HIV disease. Unfortunately the search for explanatory factors for nonadherence is still not fully developed, particularly in the area of religion and spirituality. Extant literature suggests that church attendance, religious practices and spiritual beliefs may improve health and generally benefit patients. However, religious beliefs may also play a negative role in treatment adherence due to the stigma attached to HIV d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 51 publications
1
61
0
2
Order By: Relevance
“…This approach has been used to identify culturally relevant psychosocial issues and social context variables influencing lifestyle behavior, especially diet and physical activity of African-American women with type 2 diabetes 7 . Another study among young adults used eight groups which separated men and women 17 . A study by Leeman et al employed 10 focus groups among 70 adults African-American women to design a culture and function specific of self-care intervention through one-to-one encounters with the nurse 18 .…”
Section: Qualitative Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has been used to identify culturally relevant psychosocial issues and social context variables influencing lifestyle behavior, especially diet and physical activity of African-American women with type 2 diabetes 7 . Another study among young adults used eight groups which separated men and women 17 . A study by Leeman et al employed 10 focus groups among 70 adults African-American women to design a culture and function specific of self-care intervention through one-to-one encounters with the nurse 18 .…”
Section: Qualitative Methodsmentioning
confidence: 99%
“…Religious coping has been regarded as an important strategy in dealing with calamities 41 , maintainingselfacceptance 29 ,to facilitate beneficial resolution against psychological impacts of negative life events 7,38 or to enhance self-empowerment in managing ill-health condition 2,17,46,47 . Furthermore, Baldacchino and Draper argue that due to the more general and universal meaning of spirituality; spiritual coping can be referred to utilizing any spiritual aspect in life, such as belief in a divine being, performing ritual acts to maintain harmony with others, as a leverage to enhance self-empowerment 48 .…”
Section: Religion and Spirituality As Coping Mechanismmentioning
confidence: 99%
“…Following Hill and colleagues, spirituality is defined herein as, "feelings, thoughts, experiences, and behaviors which arise from a search for the sacred," and religion is distinguished by its communal nature by adding to the definition "the means and methods (e.g., rituals or prescribed behaviors) of the search receive validation and support from within an identifiable group of people" (9). R/S has been related to treatment adherence in other populations (10)(11)(12)(13), and parents of children with CF have described a relationship between their spiritual beliefs and treatment adherence (14).…”
mentioning
confidence: 99%
“…These patients, falling into religious fatalism (belief that events are determined by fate) feel that God will protect them and that they do not need medication. Similarly, low adherence has been reported among highly religious subjects with certain religious beliefs negatively associated with adherence [1,8]. The reason for discontinuation was due to teachings and prophecies from religious leaders, supported with biblical scriptures, which led patients to feel that God and their faith only would heal them, not medicines.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have shown that spirituality is important to patients, and that it affects health care decision making and health care outcomes including the quality of life (QoL) [4,[6][7][8]. Spirituality and religious beliefs can create distress and increase the burden of illness, as well [1,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%